PENGARUH PENDIDIKAN PELATIHAN DAN KOMPETENSI TERHADAP KINERJA PERSONEL DIREKTORAT TINDAK PIDANA UMUM BARESKRIM POLRI DI JAKARTA - Sumarlian Sumarlian; Rachman Upe; Joned Ceilendra Saksana (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
This research was conducted at the Directorate of General Crimes at Bareskrim Polri, involving a population of 214 personnel, with a sample of 140 respondents selected using a 5% margin of error. The study aims to determine and analyze the impact of education, training, and competence on the performance of Police Civic Dittipidum Personnel. Data were collected through questionnaires distributed to respondents using probability random sampling. Quantitative data analysis was performed using multiple linear regression analysis with SPSS 22. The findings indicate that education, training, and competence each have a positive and significant effect on the performance of Police Civic Office personnel. When combined, these factors also show a positive and significant effect, with a coefficient of determination (R²) of 58.2%. The training education variable emerged as the most dominant factor influencing performance, with a constant coefficient value of 0.311. These results underscore the importance of comprehensive education and training programs in enhancing the competence and performance of police personnel, suggesting that targeted interventions in these areas can lead to significant improvements in their effectiveness